2023
DOI: 10.1007/s10461-023-04202-0
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Long-Acting PrEP Products Among Women and Girls: A Quantitative Survey and Discrete Choice Experiment in Eswatini, Kenya, and South Africa

Kristen M. Little,
Homaira Hanif,
Sharon M. Anderson
et al.

Abstract: While oral pre-exposure prophylaxis (PrEP) can substantially reduce HIV risk, there are important barriers to uptake and adherence. We explored preferences for long-acting injectable and implantable PrEP among women and girls in Eswatini, Kenya, and South Africa. We conducted an online quantitative survey and discrete choice experiment (DCE) among adolescent girls (15–17), young women (18–29), and adult women (30–49). Participants completed a survey about their demographics and behavior and a DCE with 5 attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Our findings confirm that, when looking at products that require consistent use, there is a preference among women for prevention methods that are long-acting, that provide dual protection, and have minimal side effects ( 16 18 , 29 , 30 , 32 , 34 36 ). Whilst having minimal side effects was noted to be of high importance to women in this study, and has been raised as a concern among young women in prior research ( 37 ), women may be willing to accept some product side effects if they are adequately counselled and supported to manage them ( 38 ).…”
Section: Discussionsupporting
confidence: 79%
“…Our findings confirm that, when looking at products that require consistent use, there is a preference among women for prevention methods that are long-acting, that provide dual protection, and have minimal side effects ( 16 18 , 29 , 30 , 32 , 34 36 ). Whilst having minimal side effects was noted to be of high importance to women in this study, and has been raised as a concern among young women in prior research ( 37 ), women may be willing to accept some product side effects if they are adequately counselled and supported to manage them ( 38 ).…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies among young people in Eastern and Southern Africa have also reported higher preference for long-acting PrEP methods ( 9 , 12 , 25 , 31 ). It is therefore not surprising that AGYW in the current study suggested that a longer acting pill and vaginal ring would be more appealing, as accessibility of methods and compliance make daily or frequently administered regimens challenging in this population of AGYW.…”
Section: Discussionmentioning
confidence: 78%
“…Another possible reason for the low uptake and adherence to oral PrEP among AGYW in Eastern and Southern Africa is that AGYW may have diverse preferences and needs regarding PrEP that are not sufficiently addressed by oral PrEP. Indeed, some studies from this region have indicated that young people may prefer PrEP products with longer duration of protection than oral PrEP ( 9–12 ) which also ensure high adherence. A previous study among AGYW in Kampala, Uganda, showed that a reported preference for oral PrEP over other PrEP methods was associated with higher oral PrEP uptake ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Study characteristics are summarised in Table 1. Most studies were crosssectional (22) including nine discrete choice experiments (DCEs). Most or all individuals in 11 studies had prior experience with oral PrEP, while nine studies were conducted among exclusively PrEP-naïve participants (Table S2).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Since implants are already a common modality for extended-release contraceptives, a device which combines the two could be attractive to women seeking protection from both HIV and pregnancy. [7,15,17,[20][21][22][23][24].…”
Section: Womenmentioning
confidence: 99%